Exploring the Correlation Between Psychological Well-Being and Hope: Evidence from Vocational Students in Indonesia - Wiwaha, Garneta Prameswari; Priyatama, Aditya Nanda (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2025)
Vocational high school students face challenges in planning their future, whether choosing to work or continue their education. Hope is a crucial factor in determining future steps, which can be influenced by psychological well-being. This study aims to examine the relationship between psychological well-being and hope among 11th-grade students at SMKN 7 Surakarta. The results of this study can encourage educational institutions and teachers to pay more attention to students' psychological well-being. This research employs a quantitative method using Pearson’s Product Moment correlation technique. The sample consists of 276 students selected through simple random sampling. The instruments used are the Adult Hope Scale (AHS) based on Snyder’s theory and the Psychological Well-Being Scale (PWB) based on Ryff’s theory. The results indicate a positive and significant relationship between psychological well-being and hope (r = 0.285, p < 0.05), although categorized as weak. Additional analysis reveals significant differences in hope based on gender and study program but not age. Male students exhibit higher hope levels than female students, while students in the Tourism Services program have the highest average hope scores, and those in Broadcasting and Film have the lowest. In conclusion, psychological well-being contributes to hope, but other factors also play a role, suggesting that future research should explore additional aspects.